2021
DOI: 10.3390/microorganisms9081640
|View full text |Cite
|
Sign up to set email alerts
|

Bonsecamin: A New Cyclic Pentapeptide Discovered through Heterologous Expression of a Cryptic Gene Cluster

Abstract: The intriguing structural complexity of molecules produced by natural organisms is uncontested. Natural scaffolds serve as an important basis for the development of molecules with broad applications, e.g., therapeutics or agrochemicals. Research in recent decades has demonstrated that by means of classic metabolite extraction from microbes only a small portion of natural products can be accessed. The use of genome mining and heterologous expression approaches represents a promising way to discover new natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…For the studies reviewed here, the rationale for BGC selection was based either on a) predicted structural novelty, b) biosynthetic class, c) structure similarity to known antibiotic class or d) biological activity of library clone (Figure 2A). The most frequent approach (56%) was to prioritize novelty by expressing unusual BGCs found in rare and/or understudied bacteria, exemplified by the discovery of the lanthipeptide marinsedin from Marinicella sedimis (Han et al 2022), and by the discovery of 31 other compounds listed in SI Table S1 (Hashimoto et al 2021;Hao et al 2019;Zhang et al 2021;Lasch et al 2021;Enghiad et al 2021;Shi et al 2019;Yuet et al 2020;De Rond, Asay, and Moore 2021;Wang et al 2023;Liu et al 2021;Lasch, Stierhof, et al 2020;Li et al 2020;Myronovskyi et al 2018;Gao et al 2023;Cheng et al 2023;Koos and Link 2019;Kaweewan, Nakagawa, and Kodani 2021;S. H. Liu et al 2019;Shuai et al 2020;Lasch, Gummerlich, et al 2020;Paulus et al 2022;Bothwell et al 2021;Gummerlich et al 2020;Alberti et al 2019;Vermeulen et al 2022;Zhang et al 2021;Unno et al 2020).…”
Section: Bgc Prioritization Biosynthetic Class and Host Taxamentioning
confidence: 99%
“…For the studies reviewed here, the rationale for BGC selection was based either on a) predicted structural novelty, b) biosynthetic class, c) structure similarity to known antibiotic class or d) biological activity of library clone (Figure 2A). The most frequent approach (56%) was to prioritize novelty by expressing unusual BGCs found in rare and/or understudied bacteria, exemplified by the discovery of the lanthipeptide marinsedin from Marinicella sedimis (Han et al 2022), and by the discovery of 31 other compounds listed in SI Table S1 (Hashimoto et al 2021;Hao et al 2019;Zhang et al 2021;Lasch et al 2021;Enghiad et al 2021;Shi et al 2019;Yuet et al 2020;De Rond, Asay, and Moore 2021;Wang et al 2023;Liu et al 2021;Lasch, Stierhof, et al 2020;Li et al 2020;Myronovskyi et al 2018;Gao et al 2023;Cheng et al 2023;Koos and Link 2019;Kaweewan, Nakagawa, and Kodani 2021;S. H. Liu et al 2019;Shuai et al 2020;Lasch, Gummerlich, et al 2020;Paulus et al 2022;Bothwell et al 2021;Gummerlich et al 2020;Alberti et al 2019;Vermeulen et al 2022;Zhang et al 2021;Unno et al 2020).…”
Section: Bgc Prioritization Biosynthetic Class and Host Taxamentioning
confidence: 99%
“…These developments led to the discovery of cryptic biosynthetic gene clusters (BGCs) in Streptomyces coelicolor two decades ago and revealed an abundance of new natural products hidden in the genomes of streptomycetes . Previous work has shown that activation of cryptic BGCs by heterologous expression in optimized host strains such as Streptomyces lividans Δ8 and Streptomyces albus Δ14 is a powerful tool to unlock this potential. In this work, genome mining, heterologous expression, and dereplication were used to identify new natural product scaffolds from the less studied strain Streptomyces aureus LU18118. This led to the discovery of new threonine-16:0dioic acids named lipothrenins and the corresponding BGC, named lit -cluster.…”
mentioning
confidence: 99%
“…Bacteria and fungi produce many of these compounds as a courtesy of nonribosomal biosynthetic enzymatic pathways, which involve multimodular megaenzymes named nonribosomal peptide synthetases (NRPSs). This Special Issue includes a review highlighting recent progress in understanding the complexity of the mechanisms of nonribosomal synthesis [ 1 ], and five research articles describing the successful discovery of new nonribosomal peptides [ 2 , 3 , 4 , 5 ], their structural characterization [ 3 , 5 ], and their relationship with the taxonomic position of the producing strains [ 6 ].…”
mentioning
confidence: 99%
“…Interestingly, four out the five research articles describe nonribosomal peptide synthesis mechanisms that mainly work out of the canonical rules. The in silico analysis of nonribosomal BGCs, together with heterologous expression, represents a successful strategy that resulted in the discovery of BE-18257 antibiotics and pentaminomycins [ 2 ], cyclic depsibosamycins [ 3 ], and bonsecamin [ 4 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation